Kecukupan Modal, Risiko Kredit, Rasio BOPO, dan Likuiditas pada Profitabilitas Bank - Wisaputri, Anak Agung Istri Vita; Ramantha, I Wayan (E-Jurnal Akuntansi, 2021)
Profitability is the ability of a bank to make a profit through the use of its assets. The health and stability of a bank is very important for the country's economy as well as for the business sector and for its customers. Banking financial ratios can be used to assess a bank's soundness. The purpose of this research is to gather empirical evidence about the impact of Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), Operational Cost of Operating Income (BOPO), and Loan to Deposit Ratio (LDR) on the profitability of conventional banks listed on the Indonesia Stock Exchange from 2017 to 2019. The research was carried out by examining the annual financial reports available on the IDX website. Purposive sampling was used as the sampling method. This study's sample consisted of 40 banking institutions. Multiple linear regression is used in the data analysis technique. Better capital adequacy and liquidity increased banking companies' ability to generate profits, according to the findings. Meanwhile, higher credit risk and BOPO ratios can limit a bank's ability to generate profits. Keywords: Capital Adequacy; Credit Risk; BOPO; Liquidity; Profitability.